Outcomes of short‐duration antiviral prophylaxis for hepatitis C positive donor kidney transplants. Issue 11 (26th July 2021) - Gupta, Gaurav; Yakubu, Idris; Zhang, Yiran; Kimball, Pamela; Kang, Le; Mitchell, Kimberly; Ijioma, Stephen; Carroll, Norman; Patterson, Julie; Shinbashi, Meagan; Kumar, Dhiren; Moinuddin, Irfan; et al.
Abstract : Trials describing 4‐ to 12‐week courses of direct‐acting antiviral drugs (DAAs) to treat hepatitis C virus (HCV) transmission from infected donors to uninfected kidney transplant recipients (D+/R− transplants) may be limited in "real‐world" application by costs and delayed access to DAAs. We previously reported HCV transmission of 13% among D+/R− transplants with 2‐ to 4‐day pangenotypic sofosbuvir/velpatasvir (SOF/VEL) perioperative prophylaxis, where one patient with HCV transmission was a nonresponder to first‐line full‐course DAA. Here, we report new data with a 7‐day prophylaxis protocol ( N  = 50), as well as cumulative treatment and outcome data on all HCV D+/R− transplants ( N  = 102). Overall, nine patients (9/102; 9%; 95% CI: 5%–16%) developed HCV transmission, with a significant decline noted in the 7‐day group (2/50; 4%; 95% CI: 0%–13%) compared with 2‐ to 4‐day prophylaxis (7/52; 13%; 95% CI: 5%–25%). All patients with HCV transmission achieved sustained virologic response post full‐course therapy (including one nonresponder from initial trial). A 1:1 matched analysis ( N  = 102) with contemporary HCV D−/R− transplants (controls) showed that although the pretransplant wait time was significantly shorter for D+/R− compared with D−/R− (mean: 1.8 vs. 4.4 years; p  < .001), there were no differences in infections, rejection, development of de novo donor‐specific antibody, or transplant outcomes up to 6 months of transplant. Abstract : Perioperative prophylaxis using 7 days of a direct‐acting antiviral drug regimen achieves a very low viral transmission rate from hepatitis C viremic donors to naïve kidney transplant recipients who, when compared to a matched cohort that received kidneys from hepatitis C negative donors, experience shorter wait times and equivalent posttransplant outcomes.